Blood component use in critical care in patients with COVID‐19 infection: a single‐centre experience. (21st October 2020) - Doyle, Andrew J.; Danaee, Anicee; Furtado, Charlene I.; Miller, Scott; Maggs, Tim; Robinson, Susan E.; Retter, Andrew
Summary: There has been a significant surge in admissions to critical care during the coronavirus disease 2019 (COVID‐19) pandemic. At present, the demands on blood components have not been described. We reviewed their use during the first 6 weeks of the outbreak from 3 March 2020 in a tertiary‐level critical care department providing venovenous extracorporeal membrane oxygenation (vv‐ECMO). A total of 265 patients were reviewed, with 235 not requiring ECMO and 30 requiring vv‐ECMO. In total, 50 patients required blood components during their critical care admission. Red cell concentrates were the most frequently transfused component in COVID‐19‐infected patients with higher rates of use during vv‐ECMO. The use of fresh frozen plasma, cryoprecipitate and platelet transfusions was low in a period prior to the use of convalescent plasma.